Slow radiation-driven wind solutions of A-type supergiants - Curé, M. (2011)
The theory of radiation-driven winds succeeded in describing terminal velocities and mass-loss rates of massive stars. However, for A-type supergiants the standard m-CAK solution predicts values of mass loss and terminal velocity higher than the observed values. Based on the existence of a slow wind solution in fast rotating massive stars, we explore numerically the parameter space of radiation-driven flows to search for new wind solutions in slowly rotating stars that could explain the origin of these discrepancies. We solve the one-dimensional hydrodynamical equation of rotating radiation-driven winds at different stellar latitudes and explore the influence of ionization changes throughout the wind in the velocity profile. We have found that for particular sets of stellar and line-force parameters, a new slow solution exists over the entire star when the rotational speed is slow or even zero. In the case of slow rotating A-type supergiant stars, the presence of this novel slow solution at all latitudes leads to mass losses and wind terminal velocities which are in agreement with the observed values. The theoretical wind-momentum-luminosity relationship derived with these slow solutions shows very good agreement with the empirical relationship. In addition, the ratio between the terminal and escape velocities, which provides a simple way to predict stellar wind energy and momentum input into the interstellar medium, is also properly traced.